2004
DOI: 10.1097/00005176-200408000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Inflammation Measured by Fecal Neopterin in Gambian Children With Enteropathy: Association With Growth Failure, Giardia lamblia, and Intestinal Permeability

Abstract: Consistent with the theory that intestinal inflammation in tropical infants may impair growth, fecal neopterin concentrations were inversely associated with growth. Factors other than Giardia are causing enteropathy and growth failure in Gambian infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
118
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 22 publications
6
118
2
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10] Furthermore, these findings provide further validation of the use of the EE score as composite marker of EE in children. The lack of a significant association between geophagy and alpha-1-antitrypsin, myeloperoxidase, and neopterin is likely a reflection of our small sample size and the EE score representing a more comprehensive measure of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8][9][10] Furthermore, these findings provide further validation of the use of the EE score as composite marker of EE in children. The lack of a significant association between geophagy and alpha-1-antitrypsin, myeloperoxidase, and neopterin is likely a reflection of our small sample size and the EE score representing a more comprehensive measure of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 59%
“…18,19 In Campbell and others, fecal neopterin, thought to occur from cell-mediated inflammation in the intestinal tract, was found to be negatively associated with height and weight gains in infants. 5 Consistent with these findings, a recent multisite study of eight countries found a significant association between fecal myeloperoxidase, alpha-1-antitrypsin, and neopterin and declines in length-forage z-scores. 2 In this study, these three markers were also combined to form an EE disease activity score (0-10 points).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13] This disorder is defined by abnormal intestinal morphology, including villous atrophy and crypt hyperplasia, which leads to reduced intestinal barrier function and increased inflammation. 7,8,14 EE is thought to arise from unsanitary environmental conditions that lead to repeated exposure to enteric pathogen causing chronic infections. [15][16][17][18] There is a growing body of literature suggesting that these chronic enteric infections alter intestinal structure and function in a manner that is suboptimal for child growth.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] There is a growing body of literature suggesting that these chronic enteric infections alter intestinal structure and function in a manner that is suboptimal for child growth. [7][8][9] It is suspected that many of these infections in children are subclinical and that diarrhea only accounts for a small proportion of EE. 9,16,19 Consistent with the hypothesis that subclinical infections are an important contributor to growth deficits in children, Checkley and others found that asymptomatic cryptosporidiosis infections, although resulting in less weight loss in the month post infection than symptomatic infections, occurred twice as much, and therefore likely contributed greater overall to child growth deficits.…”
Section: Introductionmentioning
confidence: 99%